Laparoscopic remnant cholecystectomy for calculi in the remnant gallbladder following subtotal-cholecystectomy: a report of two cases - Takeshi Utsunomiya (SpringerOpen, 2021)
Abstract Two cases of laparoscopic remnant cholecystectomy using near-infrared fluorescence cholangiography (NIFC) for remnant gallbladder calculi following subtotal-cholecystectomy are reported. Case 1: a 36-year-old woman was referred to our hospital with acute abdomen. Computed tomography showed remnant gallbladder calculi, with detected no other findings as the cause of the abdominal pain. For intraoperative exploration of the biliary anatomy, 0.25 mg/kg of indocyanine green (ICG) was administered intravenously the day before the operation. NIFC clearly showed the common bile duct and enabled safe laparoscopic remnant cholecystectomy. She was free from symptoms after the operation. Case 2: a 40-year-old woman was referred to our hospital with epigastralgia due to remnant gallbladder calculi after open cholecystectomy. ICG was administered intravenously the day before the operation. Severe adhesions were observed in the upper abdominal cavity and there was tight adherence of the duodenum to the remnant gallbladder. NIFC showed a clear margin that appeared to be the margin between the duodenum and remnant gallbladder. However, dissection of the margin observed by NIFC caused perforation of the duodenum. The clear margin seen with NIFC was likely due to visualization of the gallbladder through the duodenum. Although NIFC is a useful modality for confirming the intraoperative biliary anatomy, it is important not to rely too heavily on NIFC alone, which may lead to misinterpretation of the anatomy.